Paired genomic analysis of squamous cell carcinoma transformed from EGFR-mutated lung adenocarcinoma. (August 2019) - Park, Sehhoon; Shim, Joon Ho; Lee, Boram; Cho, Inju; Park, Woong-Yang; Kim, Youjin; Lee, Se-Hoon; Choi, Yoon La; Han, Joungho; Ahn, Jin Seok; Ahn, Myung-Ju; Park, Keunchil; et al.
Highlights: This study provides evidence of a lineage transition from adenocarcinoma to SCC. Acquired genomic alterations related to the PI3K/AKT/mTOR pathway are observed. Transformed SCC harbor initial EGFR mutation which supports the lineage transition. Adjusted tumor fraction model provide the evidence of sub-clonal evolution. Abstract: Objectives: Adenocarcinoma (ADC) to squamous cell carcinoma (SCC) transformation (AST) is reported in epidermal growth factor receptor (EGFR)-mutated non–small cell lung cancer after tyrosine kinase inhibitor (TKI) failure. However, little is known about the underlying genomic changes during the AST process. Materials and methods: We retrospectively reviewed our tissue database collected after first- or second- generation EGFR TKI resistance (n = 263) and identified 3 cases of AST. The additional case was acquired from the osimertinib resistance sample. Deep target sequencing (381 genes) using paired samples from 4 patients with AST after EGFR TKI treatment was performed. The histology of each sample was confirmed by TTF-1 and p63 immunohistochemistry. The patients received first- or second-generation EGFR TKI as an initial treatment. Results: Overall incidence of AST was 1.1% (3/263). Transformed SCC acquired genomic alterations related to the PI3K/AKT/mTOR pathway, in addition to the initial EGFR mutation. In a representative case, two separate sub-clones, with a PTEN nonsense mutation and EGFR p.T790 M mutation, were observed without histologic transformation at the time of gefitinib resistance. After subsequent treatment with osimertinib, SCC transformation was observed with the disappearance of the EGFR p.T790 M mutation and acquired copy number loss in PTEN . Adopting the sub-clonal fraction model elucidates the sub-clonal evolution process of the PTEN mutant sub-clone toward AST under the background of EGFR mutation. The rest of the transformed samples also had acquired genomic alterations in PTEN, LKB1, PIK3CA, or RICTOR, which are related to the PI3K/AKT/mTOR pathway. Conclusions: Paired genomic analysis from our sample provides early clinical evidence of the ADC to SCC lineage transition that might be provoked by an alteration in the PI3K/AKT/mTOR pathway during EGFR TKI treatment. This finding could potentially broaden the known spectrum of EGFR TKI resistance mechanisms.